Role of newer imaging modalities for airway assessment in dynamic tracheal compression - Prabha Udayakumar; Madhurima Srikanti; Vinodhadevi Vijayakumar; Gunavathi Kandappan (Wolters Kluwer Medknow Publications, 2014)
Anesthetic management of a patient with tracheal stenosis is challenging. Though we have newer imaging modalities like multislice, three-dimensional computerized tomography, virtual bronchoscopy to determine the size and anatomy of the airway, it is difficult to accurately predict the distensibility of the trachea with the available preoperative tests. With our experience in this case, we believe that newer imaging modalities are just an adjunct in the assessment of the compromised airway in case of dynamic compression. Clinical assessment is very important in deciding the plan of management.